Re: Ultrasound guidance during embryo transfer: a systematic review and meta‐analysis of randomized controlled trials. D. M. Teixeira, L. A. Dassunção, C. V. R. Vieira, M. A. P. Barbosa, M. A. Coelho Neto, C. O. Nastri and W. P. Martins. Ultrasound Obstet Gynecol 2015; 45: 139–148. (February 2015) - Drakeley, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 139–148